ESSENCE AND ROLE OF STATE EXPENDITURES IN REGULATING THE DISTRIBUTION OF THE POPULATION’S INCOME (INNOVATIVE ECONOMY, 2022)
Valihura T.V. ESSENCE AND ROLE OF STATE EXPENDITURES IN REGULATING THE DISTRIBUTION OF THE POPULATION’S INCOMEPurpose. The aim of the article is to generalize the theoretical approaches to determining the essence, classification and composition of state expenditures and substantiation of their role and mechanism in regulating the distribution of population income.Methodology of research. The theoretical and methodological basis of the research is the fundamental provisions of financial science, set forth in the works of Ukrainian and foreign scientists on the issues of formation of state expenditures. The following general scientific and special methods were used in the research process: logical analysis, synthesis, theoretical generalization (in the process of distinguishing the concepts of “budget expenditures” and “budget costs”); induction, deduction, abstract and logical (when characterizing the essence of state expenditures, state purchases and social transfers); abstraction, description, comparison (to substantiate the mechanism of influence of state expenditures on improving the financial condition of the population).Findings. It has been established that, in terms of economic essence, “budget expenditures” is a broader concept than “budget costs”, since they, under the conditions of exchange for the necessary value equivalent, can be turned into expenses. It is substantiated that public purchases and social transfers are a type of public expenditure. After all, the essence of public procurement consists in the allocation of budget funds for the purchase of goods and services necessary for the functioning of state and local authorities and the population.Instead, social transfers by their content are a system of monetary or in-kind payments to the population that are not related to their participation in economic activity at the present time or in the past. A graphical interpretation of the mechanism of influence of state expenditures on the improvement of the financial condition of the population is presented.Originality. Approaches to the classification of state expenditures have been improved. According to the method of influence on the financial condition of the population, it is proposed to divide expenses into those that directly improve the financial condition of the population, and those that improve the financial condition of the population through reproductive processes.Practical value. The results of the presented research can be used in the process of forming and implementing financial policy in terms of the use of state expenditures to improve the financial condition of the population.Keywords: state expenditures, state purchases, social transfers, population income distribution.
Keywords: state expenditures; state purchases; social transfers; population income distribution